Use of an Attribute Grammar for Software Process Measurement - Atan, Rodziah (2005)
The creations of models are essential for many knowledge disciplines to explain expected results. Modelling concept is well accepted in software engineering discipline. Some software models were built either to control the development stages or to serve as a medium that gives better understanding of the actual software systems. However, there is still a lacking of software process measurement being discussed and explored by software engineers. An aim of this research is to integrate measurement in software process modelling, to show that measurement in modelling software processes is important whereby to reduce flaws in developing large software. Software process modelling has reached the level that allows software designs to be transformed into programming languages. Examples of such approaches are architecture design language (ADL) and unified modelling language (UML). Selecting a modelling technique is essential to the designers and the selection depends on the needs of the system. This research focused on IDEF3 Standard notation as its approach to design software process models. The language syntax provided by IDEF3 standard have been modified and enhanced to suit the aim of the research. This new version of IDEF3 context-free grammar is named IDEF3-SPMA language. IDEF3-SPMA language constructs and measurement metric defined in this research has been verified using attribute grammar approach. A prototype tool for automatic process model metrics calculation namely Software Process Measurement Application (SPMA) is developed to realize the definitions defined. SPMA system counts the particulars of a process model design and output a list of measurement values. Inference metrics and appropriate advices are also stated to indicate the use of the metric values. Testing and verification results indicated that with a standard notation of performing a software process model designs, the structure and relationship between processes could be clearly seen. This research also shows that automatic calculation of process model design measurement is possible using a well-defined language specification and a specific calculation tool. Several measurement metrics produced by SPMA system are such as number of calling subprocesses in the design, number of sub-junction processes and the size of a process structure.It is concluded that this research has produced an environment consisting of design notation, language constructs, a tool that enabled measurement metrics to be calculated automatically, metric inferences and appropriate advices. The specification of measurement metrics definition using attribute grammar, the SPMA tool, metric inference and metric advices are contributions of this research